Triostin A derived hybrid for simultaneous DNA binding and metal coordination - Sachs, Eike-F. (Springer Vienna, 2010)
The natural product triostin A is known as an antibiotic based on specific DNA recognition. Structurally, a bicyclic depsipeptide backbone provides a well-defined scaffold preorganizing the recognition motifs for bisintercalation. Replacing the intercalating quinoxaline moieties of triostin A by nucleobases results in a potential major groove binder. The functionalization of this DNA binding triostin A analog with a metal binding ligand system is reported, thereby generating a hybrid molecule with DNA binding and metal coordinating capability. Transition metal ions can be placed in close proximity to dsDNA by means of non-covalent interactions. The synthesis of the nucleobase-modified triostin A analog is described containing a propargylglycine for later attachment of the ligand by click-chemistry. As ligand, two [1,4,7]triazacyclononane rings were bridged by a phenol. Formation of the proposed binuclear zinc complex was confirmed for the ligand and the triostin A analog/ligand construct by high-resolution mass spectrometry. The complex as well as the respective hybrid led to stabilization of dsDNA, thus implying that metal complexation and DNA binding are independent processes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00726-010-0764-3) contains supplementary material, which is available to authorized users.